Precarious employment, job engagement and workers’ quit intention in Chinese firms in Zimbabwe - Sharon T. Rugotwi; Nhamo Mashavira; Munyaradzi Chikove; Frank R. Matenda; Mabutho Sibanda (SA Journal of Human Resource Management)
Orientation: Chinese-owned businesses in Zimbabwe are affected by high labour turnover. High labour turnover in these businesses reduces productivity, causes low employee morale, and augments recruitment and training costs.